2017
DOI: 10.1111/asj.12891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of correcting missing daily feed intake values on the genetic parameters and estimated breeding values for feeding traits in pigs

Abstract: Daily feed intake (DFI) is an important consideration for improving feed efficiency, but measurements using electronic feeder systems contain many missing and incorrect values. Therefore, we evaluated three methods for correcting missing DFI data (quadratic, orthogonal polynomial, and locally weighted (Loess) regression equations) and assessed the effects of these missing values on the genetic parameters and the estimated breeding values (EBV) for feeding traits. DFI records were obtained from 1622 Duroc pigs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Lopez et al also had an h 2 of 0.35, further supporting our values [15]. In other studies, consistent h 2 estimates were published in Duroc pigs (0.53 ± 0.15) [33], as well as in Landrace (0.54 ± 0.01) and Yorkshire pigs (0.45 ± 0.01) [14]. Other reports in different breeds showed overall agreement, presenting values between 0.38 and 0.61 [1,27,28,32,[34][35][36][37].…”
Section: Heritability Of Production Traitssupporting
confidence: 91%
See 1 more Smart Citation
“…Lopez et al also had an h 2 of 0.35, further supporting our values [15]. In other studies, consistent h 2 estimates were published in Duroc pigs (0.53 ± 0.15) [33], as well as in Landrace (0.54 ± 0.01) and Yorkshire pigs (0.45 ± 0.01) [14]. Other reports in different breeds showed overall agreement, presenting values between 0.38 and 0.61 [1,27,28,32,[34][35][36][37].…”
Section: Heritability Of Production Traitssupporting
confidence: 91%
“…There was also partial agreement with Miar et al [28], with their similar lower estimate between ADG and subcutaneous backfat depth in commercial crossbred pigs. Nonetheless, several other published figures, such as those ranging from −0.21 to −0.47 in Akanno et al [38], −0.19 in Chang et al [39] and 0.35 ± 0.18 in Ito et al [33], were found to be inconsistent with ours. In this regard, Clutter [21] stated that the genetic association of these two traits is determined by how closely each of these traits is linked to feed intake versus the ability to partition energy intake towards lean tissue development.…”
Section: Genetic Correlations Among Production Traitscontrasting
confidence: 91%
“…Using an animal model ignoring it, Ito et al. (2018) reported direct heritabilities of 0.45 for ADG, 0.53 for BF and 0.35 for LMA. Hoque et al.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, efforts have been made to improve pork productivity and quality in Duroc pig populations ( Suzuki et al, 2005a ; Ohnishi and Satoh, 2018 ; Yazaki et al, 2020 ). To achieve more efficient pork production, it is important to improve feed efficiency ( Hoque et al, 2007 ; Ito et al, 2018 ; Homma et al, 2021 ) and reproductive efficiency, such as increasing litter size ( Tomiyama et al, 2011 ; Konta et al, 2019 ; Ogawa et al, 2019b ) and using artificial insemination techniques ( González-Peña et al, 2015 , 2016 ; Krupa et al, 2020 ). In regard to semen production traits, including semen volume ( VOL ) and total number of sperm ( NUM ) per ejaculate, previous studies have estimated genetic parameters by using a repeatability animal model (0.1–0.3; Wolf, 2010 ; Marques et al, 2017 ; Zhao et al, 2019 ), and moderate heritabilities were often estimated ( Zak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%